Potential of black soldier fly (Hermetia illucens) as alternative protein source in salmonid feeds - A review - Papuc, Tudor; Boaru, Anca; Ladosi, Daniela; Struti, Danut; Georgescu, Bogdan (Indian Journal of Fisheries, 2020)
The current constant pressure on fishmeal production for aquaculture feeds stresses the need to search for alternative sources of protein. A possible protein ingredient is insect meal, being more cost effective than fishmeal and soybean meal. Black soldier fly (Hermetia illucens) larvae meal is used in many studies with positive results regarding the bioproductive performances of salmonids. The balanced amino acid profile is comparable with the one of soybean meal. The crude protein and amino acid digestibility is high and similar to that of fishmeal. For rainbow trout (Oncorhynchus mykiss), the protein biological value of the larvae is qualitatively lower than that of fishmeal. Atlantic salmon fed with experimental diets with larvae meal showed high bioproductive performances and a better protein biological value compared with salmon fed with a standard fishmeal diet. However, the nutritional quality and chemical composition of the larvae can be drastically improved through the feeding media, which make it a very interesting candidate as a substitute for fishmeal. The aim of this review is to present the current stage of H. illucens use in salmonid feeds, detailing the chemical composition and protein quality. Furthermore, the effect of larvae meal based diets on salmonids is presented.Keywords: Atlantic salmon, Larvae meal, Rainbow trout